Spatial Reconstruction of Pore‐Crack Microstructure and Its Topological Configuration Relationship With Connectivity and Pore‐Scale Flow in Coal by 3D‐XRM - Congmeng Hao; Haoyu Zhang; Xuepeng Zhang; Ruxiang Ma; Kaizhong Zhang; Xiangqian Xing (Energy Science & Engineering)
ABSTRACT In consideration of the significance of connectivity features and topological relationships within the pore‐crack network, the micro‐scale pore‐crack microstructure of intact and tectonic coals from Qinan was investigated in 3D spatial visualization using digital core technology. The results indicate that the roughly vertical distribution in intact coal microstructure regularly divides the coal matrix into several cubic blocks. Tectonism is responsible for the fundamental transformation of the microstructure, causing tectonic coals to exhibit more sporadically distributed microcracks and pore clusters. The topological sphere and stick model based on skeletonization and its quantitative connectivity parameters show that the throat lengths of Qinan coals are mainly 0–150 μm, with tectonic coals having fewer throats over 100 μm. Pore diameters in intact coals are mostly under 30 μm, while tectonic coals exceed 20 μm. Compared with intact coals, pore spaces under 2000 μm³ in tectonic coals increased from 61.38% to 71.13%, surface area increased from 69.98% to 77.76%, and coordination number also increased significantly. These quantitative parameters collectively indicate that tectonic factors promoted the formation of more minute‐scale pore spaces and significantly enhanced the connectivity between pore spaces and throats. On this basis, the pore‐scale flow simulations were carried out from the equivalent pore network model, indicating that the pressure distribution of tectonic coals in different directions could be more concentrated and uniform than intact coals with lower fluid pressure values, revealing the promotion of tectonic effects on pore‐scale fluid transport.